The Influence of Islamic Family Parenting Patterns on the Social Development of Children in West Nusa Tenggara - Saimun Saimun; Hanafi Hanafi; Ika Risma Nuansari (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research was motivated by the researchers’ attention to the lack of social skills of fostered children at the Indonesian Children’s Foundation NTB. The form of the lack of social skills of fostered children at the Indonesian Children’s Foundation NTB, can be seen from the presence of fostered children who are less able to cooperate, commit physical violence, speak rudely and so on. This study aims to determine the effect of Islamic Family Parenting on The Social Development of children at the Indonesian Children’s Foundation NTB. The research approach used in this study is a quantitative approach with a correlational research design. The results obtained after the F test using SPSS showed that Islamic Family Parenting had an effect on children’s social development with a value of Fcount = 17.026 F_table = 4.23. With a signifivant probability of Sig. = 0.000 = 0.05, wich means Ha is accpted and Ho is rejected.